Rapid detection and monitoring of human coronavirus infections. (July 2018) - Bruning, A.H.L.; Aatola, H.; Toivola, H.; Ikonen, N.; Savolainen-Kopra, C.; Blomqvist, S.; Pajkrt, D.; Wolthers, K.C.; Koskinen, J.O.
Abstract: Human coronaviruses (CoVs) are increasingly recognized as important respiratory pathogens associated with a broad range of clinical diseases. We sought to increase the insight into clinically relevant CoV infections by monitoring antigen concentrations in six confirmed CoV-positive patients using a newly developed assay for rapid detection of CoV OC43 infections. Antigen positivity lasted 3 to 6 days in secondary infections and 13 days in primary infection. CoV infections are clinically diverse, are common, and cannot be diagnosed from clinical symptoms alone.